Perception of the multidisciplinary team on the importance of dentistry in primary care for pregnant women in Brazil: integrative review (Research, Society and Development, 2022)
In the gestational period, having a gateway to the health network providing targeted care, welcoming and longitudinal monitoring is part of prenatal care to ensure health during pregnancy, generating stable conditions for childbirth and without negative impact on maternal and child health newborn. The structural axis in Primary Health Care (PHC) and the Family Health Strategy (ESF), working in prenatal care, providing comprehensive care to pregnant women and the baby, including the family nucleus in this process. In this scenario, the Patient Care Team, has a theoretical-scientific basis and legal support to provide care for prenatal care at usual risk or high risk. The objective of this research was to identify, through an integrative literature review, the perception of the multidisciplinary team on the importance of dentistry in primary care for pregnant women in Brazil. Several actions have been proposed, revealing a positive impact related to knowledge about the importance of the dentist in the multidisciplinary team of primary care, but still many teams in primary care still work in a fragmented way in the care of pregnant women.